Effects of dietary acidifier-based diet on haematology and serum biochemical indices of broilers (2009)
A trial was conducted to determine the effect of dietary Biotronics SE® supplementation on haematological and serum parameters of broilers. A total of 120 1-day old Marshall broilers were randomly distributed to four dietary treatments using completely randomized design. Chicks in treatment 1 were fed basal diet (control) while those on treatments 2, 3 and 4 were given basal deits supplemented with 0.1% oxytetracycline HCl only; 0.3% Biotronics SE® only and 0.1% oxytetracycline HCl + 0.3% Biotronics SE®, respectively. Each treatment was a duplicate of fifteen chicks per replicate. The diets were formulated to contain 3000 Kcal/kg ME and crude protein of 23% (Starter) and 20% (finishers). Variations in values obtained for haemoglobin (g/dl) (9.28, 9.69. 10.04 and 10.15) and Mean Cell Volume (MCV) (fl) (107.02, 109.38, 125.43 and 118.31) for birds fed diets 1, 2, 3 and 4., respectively were significantly (p<0.05) different while other haematological parameters measured in both phases were similar (p>0.05). The serum triglycerides (mg/dl)(23.19. 19.29, 23.93 and 19.01) and VLDL (mg/dl) (4.63, 3.85, 5.78 and 3.80) for the Starter birds fed diets 1, 2, 3 and 4, respectively were affected by dietary acidifier inclusion. The serum total proteins and Cholesterol also varied significantly for finishers birds. Generally, most serum indices measured declined in values at the finishers phase compared with corresponding values for Starter. All measured indices were within normal physiological ranges. This study revealed Biotronics SE as a suitable alternative growth promoter for the production of meat type chickens.